Enhancing the Ilizarov Apparatus: Mechanical Stiffness - Najim, Alaa A.; Hamandi, Sadiq J.; Alzubaidi, Ahmed (Al-Nahrain Journal for Engineering Sciences, 2024)
The Ilizarov system is a form of external fixation device utilized by medical professionals to aid patients who have sustained injuries from accidents, bone shortening, or nonunion of the bone. The device is fixed onto the long bone of the patient and is adjusted according to the nature of the injury. Ilizarov’s techniques are minimal invasiveness, not aggressive, spare tissues and involve little blood loss. It consists of wires that are secured to a modular circular frame and then tightened. The Ilizarov fixator is a valuable tool for treating acute fractures, especially in cases where there is bone loss and compromised soft tissue. Several studies have aimed to improve the effectiveness of Ilizarov fixation through modifications to its frame components, such as ring diameter, transosseous element diameter, ring separation, transosseous element count in each ring, and number of rings, as well as the type of transosseous element employed, including wires, full-pins, or half-pins. Furthermore, positioning of transosseous elements at the correct crossing angle without damaging the nerves and vessels while considering the intricacy of bone deformities. Recent advancements in Ilizarov fixation will be thoroughly reviewed in this manuscript, with a particular focus on improving the stiffness of the entire frame. The main objective of this review is to pinpoint the optimal configurations, with a particular focus on stiffness, in order to foster stability and ensure a successful recuperation.